Pengembangan Lembar Kerja Peserta Didik (LKPD) Mata Pelajaran IPA Berbasis Kearifan Lokal Kelas 4 SD INPRES Seringgu Merauke - Virda Ayu Arsaini; Sormin, Salman Alparis; Rudolfus Rumabay (Journal Education Innovation (JEI), 2023)
Research on Developing Student Worksheets (LKPD) for Science Subjects Based on Local Wisdom Class IV SD Inpres Seringgu Merauke. The purpose of this study was to determine the feasibility of LKPD based on local wisdom on the theme of caring for living things at SD Inpres Seringgu Merauke, to find out the response of teachers and students to LKPD based on local wisdom on the theme of caring for living things at SD Inpres Seringgu Merauke. The subjects of this study were 26 students in class IV and I homeroom teachers for class IV SD Inpres Seringgu Merauke. This research method is Research and Development (R&D) and uses the ADDIE design model. Data collection techniques were carried out using validation sheets and questionnaires. The validation results of the three validators obtained an average percentage of 77.3% in the Eligible category, the results of the teacher's response questionnaire obtained a percentage of 100% in the very good category and the results of the student response questionnaire obtained a percentage of 90% in the very good category. Based on the results of this study, it can be concluded that the LKPD based on local wisdom on the theme of caring for living things can be used as one of the teaching materials at SD Inpres Seringgu Merauke.